Impressions of Recording a Brief Audio File Known as a TIMS (This is My Story) File - Elizabeth Tracey BCCC, MS; Jason Wilson MA, CIP; Rohan Mathur MD, MPA; David Hager MD, PhD (Journal of Patient Experience)
TIMS (This is My Story) audio files are about 1.5 min long and provide a brief snapshot of the patient as a person. Previous research has shown TIMS files improve communication between medical teams, patients and loved ones, and increase empathy on the part of clinicians for the patient. This study aims to assess what the experience of recording a TIMS file is like for the patient or their loved one, if they record on the patient's behalf. The person who recorded the file was asked to agree or disagree with 7 adjectives to describe the TIMS recording process, with a single open-ended question where they were invited to use their own descriptors. The majority of participants found the process easy, thought-provoking, unique, and unusual. Some said it was uncomfortable and about a fifth said they didn’t think it was relevant to their care.